Microbiota of Chickens and Their Environment in Commercial Production - Rychlik, Ivan; Karasova, Daniela; Crhanova, Magdalena (Avian diseases, 2023)
Chickens in commercial production are subjected to constant interaction with their environment, including the exchange of microbiota. In this review, we therefore focused on microbiota composition in different niches along the whole line of chicken production. We included a comparison of microbiota of intact eggshells, eggshell waste from hatcheries, bedding, drinking water, feed, litter, poultry house air and chicken skin, trachea, crop, small intestine, and cecum. Such a comparison showed the most frequent interactions and allowed for the identification of microbiota members that are the most characteristic for each type of sample as well as those that are the most widespread in chicken production. Not surprisingly, Escherichia coli was the most widely distributed species in chicken production, although its dominance was in the external aerobic environment and not in the intestinal tract. Other broadly distributed species included Ruminococcus torque, Clostridium disporicum, and different Lactobacillus species. The consequence and meaning of these and other observations are evaluated and discussed.
Keywords: chicken; RNA, Ribosomal, 16S; microbiota; cékum; nemoci drůbeže; drůbež; bedding; kur domácí; environment; Microbiota; mikrobiota; Escherichia coli; RNA ribozomální 16S; Chickens; zvířata; Poultry; crop; Poultry Diseases; feed; litter; Cecum; cecum; Animals